Multibeam bathymetry processed data (Reson SeaBat 7125 entire dataset, raw data converted to GIS compatible data formats) of RV PENALND during cruise NP1, Neptune Pass, United States of America - Kolker, Alexander; Weathers, Dallon; Christy, Swann; Alisha, Renfro (PANGAEA, 2025)
This dataset provides high-resolution bathymetric data of Neptune Pass, the largest new distributary of the Mississippi River, located in southeastern Louisiana, USA. Data were collected on 6 June 2022 to investigate the geomorphic evolution of Neptune Pass and to support the development of a sediment budget comparing erosion in Neptune Pass to deposition in Quarantine Bay. The survey area extends from 29.390334°N to 29.355576°N latitude and from -89.513995°W to -89.503076°W longitude. Data were acquired using a Reson SeaBat 7125 SV2 multibeam sonar system, integrated with a Position and Orientation System for Marine Vessels (POS MV) for accurate navigation and motion compensation. Survey operations and data acquisition were conducted using Qinsy hydrographic software.
Keywords: Neptune Pass